Metaverso como ambiente de trabalho para times ágeis: uma proposta de requisitos de design - Oliveira, Fabricio Malta de (Universidade Federal de São Carlos, 2025)
In recent years, remote work in software development has become increasingly common, driving the search for solutions that enhance communication and collaboration among distributed teams. Within this context, the metaverse emerges as a promising alternative by offering a three-dimensional, immersive, and persistent virtual environment capable of making remote experiences more similar to face-to-face interactions. Although Scrum is widely adopted, its use in remote settings remains focused on Distributed Agile Development through traditional two-dimensional tools, revealing a gap regarding its implementation in the metaverse. This study proposes a set of design requirements to adapt Scrum for the metaverse, aiming to optimize collaboration in remote software teams. The research was structured into five main stages: a literature review to identify related studies; an exploratory study to characterize the metaverse and its applications; an analysis of challenges faced by distributed teams to inform Scrum requirements; the proposal of design requirements followed by prototyping; and finally, an evaluation of these requirements with professionals in the field. The exploratory study identified key characteristics of the metaverse, such as immersive space, along with attributes like personalization, interoperability, and compatibility with immersive technologies. A subsequent literature review on the challenges of remote agile teams supported the definition of both cross-cutting requirements—such as faithful presence through avatars—and specific requirements for Scrum ceremonies, including sprint planning. The prototype featured avatars, 3D kanban boards, and interactive tools, and was evaluated by 12 experienced software development professionals. Quantitative analysis using the Igroup Presence Questionnaire (IPQ) revealed a high perception of spatial presence, while semi-structured interviews highlighted benefits such as increased focus, improved collaboration, and enhanced team cohesion. The findings suggest that the metaverse can help remote teams more closely approximate the dynamics of in-person work.
Metaverse as a work environment for agile teams: a design requirements proposal
Keywords: Metaverso; Scrum; Ambiente virtual colaborativo; CIENCIAS EXATAS E DA TERRA; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO